Electrodeposition of metal nanostructures for plasmonic sensing - Mueller, Aaron David (2019)
In this thesis, a cost-effective method for top-down fabrication of metallic nanostructures with deep-subwavelength dimensions is explored, finding use in plasmonic sensing applications. Currently, few methods exist for the fabrication of such metallic structures with deep sub-optical-wavelength feature sizes. The two-step process of electron beam lithography followed by electrodeposition has emerged as a viable fabrication scheme for such devices, saving both time and precious metal by avoiding physical deposition in a vacuum chamber. The development of a process which uses a transparent conductive layer of indium tin oxide rather than a metal seed layer is reported. The simulation and fabrication results of various types of high aspect ratio periodic structures, chosen for light localization and polarization invariance, are presented and analyzed, including structure morphology and the accompanying process limitations. In the case of gammadion crosses, electrodeposition produces structures with transmission spectral resonance exhibiting a Q-factor as high as 11.1 in the visible spectrum, a 65% increase over the planar counterpart. Moreover, dimers grown with this method were found to have consistently sub-10-nm and even sub-5-nm gaps. As this process can produce tall nanostructures, plasmonic modal evolution with height is investigated, along with effects on refractive index sensitivity. Tall v¬-shaped split ring resonator structures were found to have a sensitivity of close to 400 nm/RIU in the optical spectrum, much higher than the theoretical maximum predicted for simple localized resonance.